What Does Soluble C-Type Lectin-like Receptor 2 (sCLEC-2) × D-Dimer/Platelet (PLT) (sCLEC-2 × D-Dimer/PLT) Mean for Coagulation/Fibrinolysis Conditions? Comment on Yamamoto et al. Super Formula for Diagnosing Disseminated Intravascular Coagulation Using Soluble C-Type Lectin-like Receptor 2. Diagnostics 2023, 13, 2299 - Ishikura, Hiroyasu (Diagnostics, 2023)
Additionally, sCLEC-2 concentrations are likely to be affected by the platelet count. [...]this level could remain low under a low platelet count and would not increase immediately. [...]my research group proposed calculating the sCLEC-2/platelet count ratio (called the C2PAC index) to determine sCLEC2 concentrations per platelet unit and considered this index an index of platelet activation [2]. In all underlying diseases, except for patients with unidentified clinical syndromes, patients with post-cardiopulmonary arrest showed different platelet counts, values of coagulation/fibrinolytic markers, and DIC scores compared with those with other underlying diseases (Table 1) [1]. The subject study protocol (2019-K9) was approved by the Human Ethics Review Committee of Mie Prefectural General Medical Center, and informed consent was obtained from each participant.